A preliminary study on topical ozonated oil in the therapeutic management of atopic dermatitis in murine. (3rd October 2018) - Lu, J.; Chen, M.; Gao, L.; Cheng, Q.; Xiang, Y.; Huang, J.; Wu, K.; Huang, J.; Li, M.
Abstract: Objective: To explore whether ozonated oil recovery atopic dermatitis (AD) via immunoregulation. Methods: Mice were repeatedly challenged with the triplex allergens of staphylococcal enterotoxin B, ovalbumin and calcipotriol ointment on the back to develop AD lesions, and were treated with ozonated oil. The lesional skins were scanned by reflectance confocal microscopy to measure the thickness of epidermis. The skin tissues were stained. Th1-type and Th2-type cytokines in serum and in tissues were detected by ELISA and real-time PCR, respectively. Results: Ozonated oil significantly inhibited inflammation and healed the lesions in 7 d. Ozonated oil inhibited NGF expression as compared to the groups treated with vehicle or PBS ( p  < .01).The serum proteins and lesional transcripts of Th2 cytokines including IL-4 and IL-31 were lower in the ozonated oil treated group than the groups treated with vehicle or PBS ( p  < .05). The IL-10 level was increased with treatment of ozonated oil ( p  < .01). On the other hand, the expressions of Th1 cytokines including IL-2, TNF-α, and IFN-γ in the serum were not regulated by ozonated oil. Conclusions: Our results showed that ozonated oil could suppress inflammation in an AD murine via decreasing Th2-dominant cytokines response and increasing IL-10 expression. These suggest that ozonated oil may be a potential remedy for AD. Graphical Abstract: